Lightweight enterprise architectures - Theuerkorn, Fenix (Auerbach Publications, 2004)
This book provides a methodology and philosophy that organizations can easily adopt without the pitfalls of traditional architectural styles. This systematic approach uses the right balance of tools and techniques to help an enterprise successfully develop its architecture. The first section of the text focuses on how enterprises deploy architecture and how architecture is an evolving discipline. The second section introduces LEA, detailing a structure that supports architecture and benefits all stakeholders. The book concludes by explaining the approach needed to put the framework into practice, analyzing deployment issues and how the architecture is involved throughout the lifecycle of projects and systems